사고 구술(Think-aloud)을 활용한 영문법 학습: 학습자 경험을 중심으로 - 함정현(Jung Hyun Ham); 김성연(Sung Yeon Kim) (영어학, 2022)
This study explored if and to what extent think-aloud (TA) protocols could be used as a tool for teaching grammar with low-level learners in an after-school English program. For data collection, ten students took a pretest that measured their knowledge of grammatical forms. They were then directed to explain their thought processes in L1 while learning target structures, and these think-aloud episodes were audio-recorded and submitted to their teacher. After completing each TA task, the students wrote a learning journal. At the end of the two-week term, they then took a post-test and participated in a one-on-one interview. The findings of the study indicate that more than half of the students positively rated their experiences of performing TA tasks, in that the tasks allowed them to review, reflect, and recall the target structures. Interestingly, the student whose TA output was most specific and detailed made the biggest progress in the posttest. Although some students expressed confusion when having to deal with similar structures or forms with subtle differences, many students reported that the TA tasks eased their tension in learning grammar and allowed them to use cognitive, metacognitive, and social strategies while performing grammar tasks. KCI Citation Count: 1